Caribbean Slave Revolts and the British Abolitionist Movement - Matthews, Gelien (Book collections on Project MUSE., 2006)
In this illuminating study, Gelien Matthews demonstrates how slave rebellions in the British West Indies influenced the tactics of abolitionists in England and how the rhetoric and actions of the abolitionists emboldened slaves. Moving between the world of the British Parliament and the realm of Caribbean plantations, Matthews reveals a transatlantic dialectic of antislavery agitation and slave insurrection that eventually influenced the dismantling of slavery in British-held territories. Focusing on slave revolts that took place in Barbados in 1816, in Demerara in 1823, and in Jamaica in 1831-